2019
DOI: 10.3389/fpls.2019.00733
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormone Profiling Method for Rice: Effects of GA20ox Mutation on the Gibberellin Content of Japonica Rice Varieties

Abstract: Gibberellins (GAs) are a very important group of phytohormones involved in seed germination, vegetative growth, flowering, and fruit development, being only 4 of the 136 known bioactives: GA 1 , GA 3 , GA 4 , and GA 7 . It has been evidenced that mutations in the OsGA20ox-2 gene produce rice ( Oryza sativa ) dwarf varieties, which were one of the main pillars of the green re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In the current study, over time, the GAs showed a tendency to elevate from the vegetative to the generative phase. This result was similar to López-Cristoffanini et al (2019), who reported that in Oryza sativa var. japonica cv.…”
Section: Roles Of Indole-3-acetic Acid Gibberellic Acids and Salicyli...supporting
confidence: 92%
“…In the current study, over time, the GAs showed a tendency to elevate from the vegetative to the generative phase. This result was similar to López-Cristoffanini et al (2019), who reported that in Oryza sativa var. japonica cv.…”
Section: Roles Of Indole-3-acetic Acid Gibberellic Acids and Salicyli...supporting
confidence: 92%
“…Ten local varieties tested also showed differences in height Ten local varieties tested also showed differences in height [35]. Application GA on three varieties of rice japonica mediterania NRVC980385, Bomba and Dwarf -Bomba shows that Bomba variety is significantly higher than the other two varieties [36]. 86,1 b Number followed by the same letter not significant at the 5% level by DNMRT Plant height is not only a decisive factor in plant architecture, but also an important agronomic trait that is directly linked to the harvest index and yield potential.…”
Section: Resultsmentioning
confidence: 99%
“…GA20ox, GA3ox, GA2ox and EUI1 together form a feedback transcriptional control mechanism to maintain the homeostasis of GA content in plants. Inhibition or loss of function of the GA20ox gene results in dwarfing of the plant [45,46]. This may be an important candidate gene for PH in soybean.…”
Section: Discussionmentioning
confidence: 99%